A review on the visual design styles in data storytelling based on user preferences and personality differences - Sheikh Abdul Aziz, Madihah; Mohd Zanan, Muhammad Faris Basheer (IEEE, 2022)
The proliferation of data analytics has led to a vast application of data visualization and storytelling in a variety of disciplines extending across banking, sports to healthcare. Data, information, and knowledge are transformed into interactive visual representations that convey a meaningful story. In big data analytics, relevant and high-quality graphical insights ought to be factually accurate and relevant to make a key decision. Data storytelling has become an effective way to apply information visualization as it can enhance communication effectiveness. Using visualization as a tool to enhance narrative for the viewers in enforcing data storytelling as a way to understand data and information. Findings suggest that an individual's personality variations correspond strongly with a user's preference toward visual design styles for visualization and storytelling. This paper investigates previous studies regarding personality, information visualization, narrative, and storytelling, as well as their interrelationships through online databases. The futuredirection of the present study.